Betamethasone therapy in ataxia telangiectasia: unraveling the rationale of this serendipitous observation on the basis of the pathogenesis. Issue 5 (4th November 2012) - Giardino, G.; Fusco, A.; Romano, R.; Gallo, V.; Maio, F.; Esposito, T.; Palamaro, L.; Parenti, G.; Salerno, M. C.; Vajro, P.; Pignata, C.
<x xml:space="preserve">Abstract</x> Ataxia telangiectasia (A‐T) is a rare autosomal recessive disorder characterized by progressive neurological dysfunction. To date, only supportive care aimed to halt the progressive neurodegeneration is available for the treatment. Recently, an improvement of neurological signs during short‐term treatment with betamethasone has been reported. To date, the molecular and biochemical mechanisms by which the steroid produces such effects have not yet been elucidated. Therefore, a review of the literature was carried out to define the potential molecular and functional targets of the steroid effects in A‐T. Glucocorticoids (GCs) are capable of diffusing into the CNS by crossing the blood–brain barrier (BBB) where they exert effects on the suppression of inflammation or as antioxidant. GCs have been shown to protect post‐mitotic neurons from apoptosis. Eventually, GCs may also modulate synaptic plasticity. A better understanding of the mechanisms of action of GCs in the brain is needed, because in A‐T during the initial phase of cell loss the neurological impairment may be rescued by interfering in the biochemical pathways. This would open a new window of intervention in this so far incurable disease.